Targeted sequencing using a 47 gene multiple myeloma mutation panel (M3P) in ‐17p high risk disease. (10th October 2014) - Kortüm, Klaus M.; Langer, Christian; Monge, Jorge; Bruins, Laura; Egan, Jan B.; Zhu, Yuan X.; Shi, Chang Xin; Jedlowski, Patrick; Schmidt, Jessica; Ojha, Juhi; Bullinger, Lars; Liebisch, Peter; et al.
Summary We constructed a multiple myeloma (MM)‐specific gene panel for targeted sequencing and investigated 72 untreated high‐risk (del17p) MM patients. Mutations were identified in 78% of the patients. While the majority of studied genes were mutated at similar frequency to published literature, the prevalence of TP53 mutation was increased (28%) and no mutations were found in FAM46C. This study provides a comprehensive insight into the mutational landscape of del17p high‐risk MM. Additionally, our work demonstrates the practical use of a customized sequencing panel, as an easy, cheap and fast approach to characterize the mutational profile of MM.